Contribution to the Method of Local Blood Flow Determination in Rats by Means of 86Rb - Kapitola, J.; Schreiberová, O.; Jahoda, I. (Nuklearmedizin - NuclearMedicine, 1968)
The study describes some experience with the determination of local organ blood flow by measuring tissue uptake of 86Rb in conscious rats. The values of 86Rb uptake in 16 organs and tissues of intact rats, results of control measurements in animals sacrificed 20, 40 and 60 sec after 86Rb injection and some local variations in the same organ or tissue, are presented.